Efforts to Improve Communication Skills through Spinning a Yarn Method Using Hand Puppets in Children Aged 4-5 Years at TK Kemala Bhayangkari 61 Pulung - Riva Kurniawati; Ida Yeni Rahmawati; Dian Kristiana (Universitas Muhammadiyah Ponorogo, 2020)
This study aimed to determine an increase in communication skills through spinning a yarn method using hand puppets in children aged 4-5 years at TK Kemala Bhayangkari 61 Pulung. This study is a class action research. Data collection needed to support the results of research included instruments of observation and interviews. The data obtained were described descriptively. The subjects of our study were 15 children in class A1. In the first cycle communication skills got results reaching 40%. This has increased compared to the pre-action results. In pre-action, only 20% of children was able to master the aspects of communication skills. Cycle II has improved a lot. Children who were able to master all aspects of communication skills reached 80%. From this research, it can be concluded that the use of spinning a yarn method could improve communication skills in children aged 4-5 years. This spinning a yarn method using hand puppets was able to attract the attention of children so that children were more focused and able to create fun learning.